LINGUOCULTURAL ADAPTATION OF STUDENTS FROM TURKMENISTAN TO THE RUSSIAN UNIVERSITY ENVIRONMENT - E.N. Makarova (Многоязычие в образовательном пространстве)
The relevance of the issue under study results from the course for further internationalisation of the Russian higher education and the increasing flow of students from Central Asian countries to the universities of the Russian Federation. The existing obstacles to the effective adaptation of foreign students in the Russian academic environment determine the need for further study of cross-cultural interaction issues taking into account national specifics. The aim of the paper is to analyse the linguocultural adaptation of Bachelor students from Turkmenistan to the conditions of the Russian academic environment. On the basis of a survey, the activity of their interaction with the Russian students was analysed. In the course of the study the factors complicating this process are considered. It was revealed that 40 % of the respondents had a low level of interaction with the Russian fellow-students; 20 % of the respondents did not have any interaction at all. This situation is caused by the Turkmen students’ insufficient command of the Russian language norms, as well as their low level of awareness of the Russian cultural specifics, including national traditions and customs. A high level of the readiness of the students from Turkmenistan for cross-cultural communication with the Russian students was confirmed. Joint social activities can be an effective measure to build trust between them and the representatives of the Russian student environment. A detailed analysis of the peculiarities of linguocultural adaptation of Bachelor students from Turkmenistan to the conditions of the Russian universities has not been conducted before. The obtained results are of practical value and can contribute to solving the problems of adaptation of students from Turkmenistan to the Russian educational environment.